THU0049 Development of tfh-th1 like cells through epigenetic modification by stats family factors in patients with systemic lupus erythematosus. (12th June 2018) - Ma, X.; Nakayamada, S.; Kubo, S.; Sakata, K.; Yamagata, K.; Tanaka, Y.
Abstract : Background: Systemic lupus erythematosus (SLE) is a prototype of autoimmune disease characterised by chronic immune activation and multiple immunologic phenotypes (1) . Among several types of immune cells, T follicular helper (Tfh) cells serve important roles in the development and progression of SLE (2) . Objectives: To assess the characteristics and mechanisms of differentiation of Tfh cells, we probed the phenotype of T helper cells in patients with SLE and underlying epigenetic modifications by cytokine-induced signal transducer and activators of transcription (STAT) family factors. Methods: Naive CD4 + T cells and memory CD4 + T cells were isolated and stimulated by various cytokines and T cell receptor (TCR) in vitro . Expression of characteristic markers of Tfh-Th1-cells and phosphorylation of STATs were analysed by flow cytometry and qPCR. Histone modifications were evaluated by chromatin immunoprecipitation. Peripheral blood mononuclear cells from SLE patients and healthy controls were analysed by flow cytometry and productions of cytokines in serum were tested by cytometric bead array. Results: Differentiation of CXCR5 + CXCR3 + Bcl-6 + T-bet + IL-21 + IFN-γ + Tfh-Th1-like cells was induced by IL-12. Among STAT family, STAT1 and STAT4 were phosphorylated simultaneously by IL-12 independent of IFN-γ and directly bound on Bcl-6 and T-bet gene loci accompanied by suppression of trimethylated histone 3 lysine 27. Compared with healthy controls, responsiveness of activation of STAT1 and STAT4 by IL-12 and proportion of activated Tfh-Th1-like cells were increased in patients with SLE. Conclusions: Our findings suggest that IL-12-mediated co-activation of STAT1 and STAT4 alter histone modification, resulting in development of Tfh-Th1-like cells that are characteristically expanded in patients with SLE. These findings could be one of underlying pathogenesis of SLE and potentially helpful towards development of cell-specific treatment. References: [1] Tsokos GC. Systemic lupus erythematosus. N Engl J Med. 2011;365(22):2110–21. [2] Suarez-Fueyo A, et al. T cells in systemic lupus erythematosus. Curr Opin Immunol2016;43:32–8. Acknowledgements: The authors thank Ms. N. Sakaguchi for the excellent technical assistance. Disclosure of Interest: None declared